(untitled) (Rudarsko-geološko-naftni zbornik, 2020)
In the process of oil reservoir waterflooding, natural water dump flood technology for reservoir pressure decline prevention is considered as an unconventional but technically less demanding, more economical and safer method in comparison to surface power water injection. With natural dump flood technology, a single well serves as a water producer from a water bearing layer (aquifer) and simultaneously through gravity and the pressure difference between the aquifer and the depleted oil reservoir, it serves as a water injector inside the oil reservoir without expensive and complex injecting water treatment facilities at the surface. With the use of such technology and the running of intelligent well completion, it allows for the permanent monitoring of water production, injection rates and temperature inside the chosen reservoir. In addition, in offshore operations, the use of a subsea wellhead with a mud line suspension system allows for the placing of the injector well at the best predetermined position for water injection in a targeting reservoir and, together with an efficient subsurface acoustic data acquisition system, leads to better reservoir management and well integrity improvement. The overview and critical reflection of the drilling and intelligent completion of a natural dump flooding well for reservoir pressure support in partially depleted oil reservoirs in the Persian/Arabian Gulf has been given, referring to both their preparation and execution phase. The possibility of applying natural water dump flood was also considered in the Croatian onshore Beničanci oil field through a pilot project of water injection into the Be-62 well.